Anesthesia for electroconvulsive therapy. Issue 5 (October 2018) - Soehle, Martin; Bochem, Janina
Abstract : Purpose of review: Electroconvulsive therapy (ECT) is a well established and effective therapy in treatment-resistant depression. It is performed under general anesthesia, but no consensus exists regarding the optimal anesthetic drugs. A growing interest in optimizing adjunctive medication regimes in ECT anesthesia has emerged in recent years. Moreover different methods of seizure induction have been evaluated. Recent findings: Pretreatment with dexmedetomidine eased the propofol injection pain and reduced the hyperdynamic response to ECT, but prolonged recovery. Remifentanil exhibited no proconvulsive effect and had no effect on seizure quality. Ketamine showed an antidepressive effect but was associated with cardiovascular side effects and an increased recovery time. A bispectral index-guided anesthesia or a time delay between anesthesia and seizure induction resulted in a better seizure quality presumably by avoiding high concentrations of (anticonvulsive) hypnotics. Seizure induction by magnetism seems to be an alternative to ECT, as the former is associated with less cognitive side effects but comparable antidepressive efficacy. Summary: The current practice of anesthesia for ECT should not be modified, as the evidence of studies is either too low or the results are inconsistent. Some approaches are promising but require validation in further studies with a higher number of participants.